Safety and high-recovery mechanisms and application research for initial mining of thick-coal-seam with complex structure and thick-hard roof - Zechao Chang; Xufeng Wang; Dongdong Qin; Jinzhu Yu; Xuyang Chen; Jiyao Wang; Zhijun Niu; Chenlong Qian (Scientific Reports, 2024)
Abstract Thick-coal-seam with complex structures and thick-hard roof in the initial mining phase pose various challenges, including a long weighting interval, strong rock pressure, poor top coal caving performance (TCCP), and significant coal loss. These problems directly affect the safety and efficiency of the mining operations. This study employs the principles of elastic thin plates and ellipsoidal bodies to unravel the formation mechanism of strong rock pressure in thick-hard roof and the influence of parting on the TCCP. In addition, a hydraulic fracturing technique is proposed for safe-efficient recovery during the initial mining phase. The reliability of this technique is verified through numerical simulations and field experiments. The research findings reveal the following. (1) The primary causes of strong rock pressure in the mining face are attributed to a long weighting interval and wide collapse range of the main roof, and the weighting interval is primarily influenced by the thickness and tensile strength of the main roof. (2)The key factor affecting the TCCP is the cantilever beam structure formed by the fracture of the thick-hard parting, as it intersects the ellipsoidal body during coal caving. The simultaneous fracturing of both the top coal and roof can reduce the weighting interval on the working face. This process effectively decreased the strength of the thick-hard parting within the top coal, while simultaneously enhancing its load strength and eliminating the cantilever structure resulting from the parting fracture. It not only reduces the first weighting intensity but also promotes the early and proper coal release, thereby enhancing the TCCP and ensuring safe-efficient mining during the initial mining phase. (3) Aiming at the difference in the strengths of the top coal and roof, a graded hydraulic fracturing technique and system were proposed. Fracturing boreholes with a diameter of 60 mm, spacing of 10 m, and height of 20.85 m, which can economically and effectively ensure the fracturing results. Field applications have demonstrated that fractured coal and rocks in fracturing areas exhibit well-developed fractures. During the initial mining phase, the weighting interval in the working face was reduced by 20 m, resulting in a decrease in the overburden pressure and 26.9% reduction in the lumpiness of the top coal. Additionally, the recovery rate increased by 31.19%.